The effect of water on tracking failure of epoxy/MgO samples - İSPİRLİ, MEHMET MURAT (My University, 2022)
In this study, the change in the electrical performance of epoxy/MgO, which is one of the materials used to increase the performance of epoxy resin, was evaluated under the effect of water. Accordingly, comparative tracking index (CTI) experiments, which are one of the effective methods used to model electricity\"s effect on surface properties, were used. To measure the performance of epoxy resins without additions, 1%, 3% and 5% nanosized MgO-added samples were prepared. Prepared samples were stored 24 h, 48 h, 72 h, 96 h and 120 h in pure water. Then, the samples were subjected to CTI test in a laboratory environment. Recorded leakage current from experiments was analyzed using harmonic analysis. While the experimental results obtained have resulted in improvements like those of MgO/epoxy additions previously reported in the literature, the resistance of the observed samples after their exposure to pure water has been reported, in the opposite direction. Thus, with this experimental study, it has been demonstrated that it is necessary to add some hydrophobic compounds to show the desired performance in the external environment with MgO-doped epoxy resins. It should be supported by extra protection in such dense liquid environments.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Signal Processing; Engineering and Technology; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Elektrik ve Elektronik Mühendisliği; Mühendislik (çeşitli); Fizik Bilimleri; General Engineering; Electrical and Electronic Engineering; Engineering (miscellaneous); Physical Sciences; Tracking failure; Epoxy resin; Harmonic distortion; Comparative tracking index; SURFACE DEGRADATION; SILICONE-RUBBER; LEAKAGE CURRENT; NANOCOMPOSITES; RESISTANCE; AC; Tracking failure; Epoxy resin; Harmonic distortion; Comparative tracking index